Molecular detection of static magnetic field forces on uropathogenic Escherichia coli number and fermentation activities - Jamal Azeez, Amanj; Hussein Kamel , Fouad (Diyala Journal of Medicine, 2022)
Background: The region that a magnetic force has an effect on is known as a magnetic field. Normally, two poles of this field are concentrated. Most magnetic objects are made up of a variety of tiny fields known as domains. There are many different techniques that have been published in the literature for using magnetic energy as a diagnostic tool and for treating illnesses in both humans and animals. Objective: To examine the influence of varying amounts of static magnetic field on the viability of bacteria and the fermentation of carbohydrates. Patients and Methods: Locally prepared dipolar static magnetic field of strength 400, 800, 1200 and 1600 Gauss were used in this study measured by Teslometer. Escherichia coli isolated from 75 isolates taken from the patient who had the UPE, 25 were identified as E. coli, and only (12) samples of identified E coli specifically detect changes numbers of bacteria and biochemical test, most of the sugars ferment that have be changed and the polymerase chain reaction was utilized to identify the 16SrRNA gene (PCR). Results: The inhibitory impact of SMF is attributable, according to transcriptomic analysis, to differentially expressed genes (DEGs) predominantly included in carbon source consumption. The bacterial phenotype in SMF is consistently effectively restored by adding To the cultivation conditions, add glycolate or glyoxylate, and mutants losing glycolate oxidase are no longer susceptible to static magnetic field. Conclusion: It was concluded that the magnetic field could notably obvious by exposing bacterial cells growth density will decrease and change bacterial biological activity on sugar fermentation and due to mutation.